Evaluation of Intra-articular Fracture Extension After Gunshot Wounds to the Lower Extremity: Plain Radiographs Versus Computer Tomography. Issue 6 (June 2017) - Hwang, John S.; Koury, Kenneth L.; Gorgy, George; Sirkin, Michael S.; Reilly, Mark C.; Lelkes, Valdis; Adams, Mark R.
Abstract : Objective: This study was to compare the use of computer tomography with plain radiographs for the evaluation of intra-articular extension of long bone fractures in the lower extremity after low-energy gunshot wounds. Design: Retrospective chart and radiographic review. Setting: Level 1 Trauma Center. Patients/Participants: Data were collected from a single institution from 2000 to 2014. Inclusion criteria consisted of patients greater than 17 years of age, low-velocity gunshot injuries causing fracture of the femur or tibia, plain radiographs with adequate films, and computed tomography (CT) imaging of the fracture. This consisted of 133 patients with 140 fractures. Intervention: Intra-articular fracture extension was evaluated on initial plain radiographs and CTs. Main Outcome Measures: Comparison of "gold standard" CT with all reviewers' evaluation of plain radiographs. Results: There were 140 total fractures; 108 were femoral fractures and 32 were tibial fractures. By comparing plain radiographs with the gold standard CT, the reviewers demonstrated correct diagnosis in 85% of intra-articular fractures and 96% of non–intra-articular fractures. In addition, the reviewers accurately diagnosed 70.8% of intra-articular extensions in the diaphysis and 70.5% in the metaphysis. The sensitivity and specificity for plain radiographs were 85.3% and 96.0%, respectively, for all locations. Metaphyseal and diaphyseal fractures demonstrated the poorest sensitivity at 80.7% and 82.1%, respectively. Conclusions: Low-energy gunshot wounds with fractures in the diaphyseal of the distal femur and all metaphyseal fractures warrant CT evaluation to better examine for intra-articular fracture extension. Level of Evidence: Diagnostic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.